THE BINARI {αt}-COMPONENT IN THE {(dn)α} AND {(αd)n} MODELS OF 7 Li - Afanasyeva, N. V.; Burkova, N. A.; Zhaksybekova, K. A.; Urazalin, A. A. (Recent Contributions to Physics, 2011)
Within the αdn -model for 7 Li nucleus αt relative motion wave functions have been built and spectroscopic t S -factors of tritons separation have been calculated in the binary α + t channel by usingdifferent { } 7 Li αdn wave function models.
Keywords: wave functions